Comparative toxicities of 3 platinum‐containing chemotherapy regimens in relapsed/refractory lymphoma patients. Issue 4 (5th July 2016) - Tixier, F.; Ranchon, F.; Iltis, A.; Vantard, N.; Schwiertz, V.; Bachy, E.; Bouafia‐Sauvy, F.; Sarkozy, C.; Tournamille, J. F.; Gyan, E.; Salles, G.; Rioufol, C.
Abstract: Optimal salvage chemotherapy regimen for patients with relapsed or refractory Hodgkin and non‐Hodgkin lymphoma remains unclear but often based on platinum regimens. This retrospective study assesses in real life the toxicities profiles of patients with relapsed or refractory lymphoma treated with DHA (dexamethasone, high dose aracytine cytarabine) plus platinum salt (dexamethasone‐High dose aracytine (cis)platin (DHAP), dexamethasone‐High dose aracytine carboplatin (DHAC), or dexamethasone‐High dose aracytine Oxaliplatin (DHAOX)), from February 2007 to May 2013 in 2 French hospitals. Toxicities were recorded from medical files and assessed according to the National Cancer Institute Common Toxicity Criteria version 3.0. Potential risk factors of renal insufficiency were tested by univariate analyses. A total of 276 patients were treated: 168 with DHAP (60.9%), 79 with DHAOX (28.6%), and 29 with DHAC (10.5%). Rituximab was associated in 80.1% of patients (n = 221). Renal failure was reported in 97 patients, mainly with cisplatin regimen (86.6%) leading to 8.9% grade III to IV renal failure ( P = .001). Renal insufficiency was reversible in most patients but remained persistent in 24, with all of them being treated with DHAP except 1. Cisplatin‐based regimen (50.0% versus 12.0%, P < .05) and female (44.6% versus 29.7%, P < .05) appeared to be at higher risks of renal failure. Platinum cumulative dose is a significant risk factor of nephrotoxicity. Hematologic toxicity was more frequent with carboplatin and cisplatin with at least 1 event (all toxicity grade) respectively in 79.3% and 71.4% of patients treated ( P < .005). Auditory toxicity was mainly reported with cisplatin (n = 19; 4 grade I‐II and 15 grade III‐IV). Oxaliplatin was implicated in 77.6% of neurotoxicity (n = 59), mainly moderate (grade I‐II). In conclusion, DHAOX and DHAC regimens have more favorable toxicity profile than DHAP regimen. Their lack of renal toxicity makes them attractive regimens, which may be interesting for patients eligible for autologous stem cell transplantation. Nevertheless, these results have to be confirmed by the therapeutic efficacy of these 3 regimens.